Taxonomic and functional diversity of protists in saline and hypersaline lakes in southern Western Siberia, a region strongly affected by climate change - Elena A. Gerasimova; Alexander S. Balkin; Vladimir Y. Kataev; Ekaterina S. Filonchikova; Yulia V. Mindolina; Denis V. Tikhonenkov (Water Biology and Security)
Climate change has had an unprecedented impact on lake ecosystems around the globe and has both direct and indirect consequences on lake structure and mineralization. These changes are threatening the unique biodiversity that lake ecosystems currently support. Siberia is experiencing one of the greatest impacts of climate change in the world, with exceptional warming in the north and increasing aridity in the south. Lakes in southern West Siberia, including saline and hypersaline waterbodies within endorheic basins, remain unexplored in terms of the biodiversity of the microbial eukaryotes inhabiting them. In this study, we investigated the taxonomic and functional diversity of planktonic protist communities in saline and hypersaline lakes (22–220‰) in southern Western Siberia through Illumina 18S rDNA amplicon sequencing. Taxonomic diversity was represented by the Amoebozoa, Archaeplastida, Cryptista, Excavata, Haptista, Obazoa, Provora, and TSAR supergroups, and varied significantly among lakes of different salinities. Salinity has been shown to be an important determinant that directly influences the composition and uniqueness of protist communities. The co-occurrence network analysis revealed a decrease in the complexity of the network of protist communities with increasing salinity. The taxonomic diversity of protists in lakes determines functional diversity, which is expressed as the relative abundance of free-living heterotrophs, phototrophs, and parasites. Phototrophs dominated the delta-hypersaline waters, and free-living heterotrophs dominated the alpha- and beta-hypersaline lakes. The parasite amplicon sequence variants (ASVs) were affiliated mainly with mixohaline and beta-hypersaline lakes.